A new type of composite gas phase antirust film and its manufacturing method

CN122976154APending Publication Date: 2026-10-27HUBEI TIANLI BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611004999.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-07
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]为了解决因相关的VCI膜的缓蚀剂释放为被动扩散而导致缓蚀剂过量浪费且高腐蚀环境下药剂供给不足的问题,本申请提供一种新型复合气相防锈膜及其制造方法

Benefits of technology

1、由于本申请采用氯离子触发自修复控释层与离子响应自锁定界面层相配合的层叠结构,利用层状双氢氧化物对氯离子的选择性捕获和缓蚀阴离子的等电荷置换释放,同时借助界面层中海藻酸衍生物与溶出金属离子的行为,将外部氯离子侵蚀转化为内部缓蚀剂释放和后续药量限流的触发信号,实现侵蚀响应型按需防护与自动节药的一体化调控,获得在动态腐蚀环境中自主调节防锈供给与药效保持周期的效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122976154A_ABST
    Figure CN122976154A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of rust prevention, and particularly discloses a novel composite gas-phase rust prevention film and a manufacturing method thereof. The novel composite gas-phase rust prevention film comprises a chlorine ion triggered self-repairing controlled release layer, an ion responsive self-locking interface layer, a directional hydrophobic breathing film layer and a phase change temperature adjusting layer which are stacked in sequence. The manufacturing method comprises the following steps: S1, polypropylene and a beta crystal nucleating agent are blended, extruded and cast into a sheet and stretched to obtain a base film; S2, an ion responsive self-locking interface layer coating solution is coated on the surface of the base film, and the interface layer is formed after drying; S3, after drying, the surface of the interface layer is fused into a film by extrusion casting of a blended material to form a self-repairing controlled release layer; S4, on the other surface of the base film, a phase change temperature adjusting layer is formed by extrusion casting or coating of a blended material; and S5, the novel composite gas-phase rust prevention film is obtained by winding. The gas-phase rust prevention film can be used for rust prevention of automobile engines and gears, and has the advantages of self-regulation of rust prevention supply and maintenance of drug efficacy in a dynamic corrosion environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of rust prevention technology, and more specifically, to a novel composite vapor phase rust inhibitor film and its manufacturing method. Background Technology

[0002] Vapor phase corrosion inhibitors (VPIs), as carriers of volatile corrosion inhibitor technology, are now widely used for long-distance transportation and warehousing protection of precision metal parts such as automotive engines and gears, and are one of the mainstream solutions in the field of industrial rust prevention packaging. Compared with traditional rust-preventive oil coating, vacuum packaging, desiccant filling and other protective methods, VPIs can rely on the gas phase diffusion characteristics of corrosion inhibitor molecules to cover the surface of irregularly shaped workpieces without dead corners. After unpacking, they can be directly put into production without cleaning, reducing maintenance costs. In recent years, through the optimization of multi-layer co-extrusion process and the modification of corrosion inhibitor compounding, the rust prevention cycle of conventional VPIs in dry storage environments can meet the usage requirements of most static, low-corrosion-risk scenarios.

[0003] The release of corrosion inhibitors in VCI membranes is mostly passive diffusion, with the release rate determined by the membrane porosity and ambient temperature. It cannot identify chloride ions, a triggering factor for atmospheric corrosion and salt spray corrosion, and is prone to problems of excessive waste of corrosion inhibitors in non-corrosive environments and insufficient supply of agents in highly corrosive environments. On the other hand, even if ion exchange-type response units are introduced, they can only achieve the triggered release of corrosion inhibitors. Without the construction of a self-regulating current limiting mechanism linked to the release behavior, the corrosion inhibitor will continue to escape disorderly after triggering, which not only leads to a shortened efficacy period, but also causes crystallization and secondary electrochemical corrosion on the metal surface due to excessively high local corrosion inhibitor concentrations. Summary of the Invention

[0004] To address the problems of excessive waste of corrosion inhibitors due to passive diffusion release in VCI films and insufficient supply of agents in highly corrosive environments, this application provides a novel composite vapor phase corrosion inhibitor film and its manufacturing method.

[0005] In a first aspect, this application provides a novel composite vapor phase rust inhibitor film, which adopts the following technical solution: A novel composite vapor-phase corrosion inhibitor film comprises, in sequence, a chloride ion-triggered self-healing controlled-release layer, an ion-responsive self-locking interface layer, a directional hydrophobic breathable membrane layer, and a phase change temperature-regulating layer. The chloride ion-triggered self-healing controlled-release layer comprises the following raw materials in parts by weight: 80-120 parts polyethylene and 5-30 parts intercalated modified layered double hydroxides; vapor-phase corrosion-inhibiting anions are intercalated between the layers of the intercalated modified layered double hydroxides. The ion-responsive self-locking interface layer comprises the following raw materials in parts by weight: 80-120 parts polyvinyl alcohol, 10-40 parts alginate derivative, and 5-20 parts a metal ion precipitation precursor. The directional hydrophobic breathable membrane layer comprises the following raw materials in parts by weight: 80-120 parts polypropylene and 0.1-2 parts β-crystal nucleating agent, and the directional hydrophobic breathable membrane layer is a porous membrane with non-penetrating micropores. The phase change temperature-regulating layer comprises the following raw materials in parts by weight: 80-120 parts polyolefin and 10-50 parts organic phase change microcapsules.

[0006] By adopting the above technical solution, a synergistic protection system from the inside out is constructed by stacking four functional layers in sequence. The chloride ion-triggered self-healing controlled-release layer is located in the innermost layer and directly contacts the protected metal. The gas-phase corrosion-inhibiting anions pre-inserted between the intercalated modified layered double hydroxide layers are released through ion exchange when chloride ions invade, converting the corrosion factor into a protective response signal. The ion-responsive self-locking interface layer is set on the outside of the controlled-release layer and dynamically adjusts its porosity according to the release of the corrosion inhibitor, actively limiting the ineffective dissipation of the agent. The directional hydrophobic breathing membrane layer separates the diffusion channels of the gas-phase corrosion inhibitor molecules from the formed liquid condensate, preventing condensation from scouring the active components inside the membrane. The outermost phase change temperature-regulating layer absorbs heat at high temperatures through organic phase change microcapsules, inhibiting the rapid rise of the membrane temperature and delaying the thermal loss of the gas-phase corrosion inhibitor. The four layers work together to enable the film to maintain long-term stable rust prevention capabilities under complex working conditions such as marine transportation and humid salt spray.

[0007] Preferably, the gas-phase corrosion-inhibiting anion is selected from one or more of benzoate, caprylate, laurate, or cinnamate; the layered double hydroxide is a magnesium-aluminum layered double hydroxide or a zinc-aluminum layered double hydroxide.

[0008] By adopting the above technical solution, the above-mentioned organic carboxylate ions are selected as corrosion-inhibiting anions. After volatilization, they adsorb and form a film on the metal surface, showing good corrosion inhibition effects on ferrous metals and some non-ferrous metals. Magnesium-aluminum or zinc-aluminum layered double hydroxides have a typical lamellar structure with strong interlayer anion exchange capacity. After chloride ions enter the interlayer, they are preferentially captured and fixed, while the original corrosion-inhibiting anions in the interlayer are replaced and released into the microenvironment with equal charge. This process directly converts corrosive chloride ions into the driving force that triggers the on-demand supply of corrosion inhibitors, realizing a directional response of prevention when chloride is present and no consumption when chloride is absent.

[0009] Preferably, in the ion-responsive self-locking interface layer, the alginate derivative is sodium alginate or potassium alginate, and the metal ion precipitation precursor is zinc carbonate microparticles; the average particle size of the zinc carbonate microparticles is 0.5-5 μm; and the degree of alcoholysis of the polyvinyl alcohol is greater than 85%.

[0010] By adopting the above technical solution, sodium alginate or potassium alginate molecules contain a large number of carboxyl groups, which undergo ionic cross-linking with polyvalent metal ions to form a gel network. Zinc carbonate particles remain stable under normal conditions. When the inner layer releases corrosion-inhibiting acid anions triggered by chloride ions, the acidic microenvironment causes zinc carbonate to gradually dissolve zinc ions. The zinc ions then trigger ionic cross-linking of alginate derivatives, causing the originally microporous polyvinyl alcohol matrix to form a dense hydrogel region locally, partially blocking the gas permeation channels. This establishes a negative feedback loop of corrosion-triggered release, release-induced flow restriction, and flow restriction reducing chemical consumption, enabling the film to achieve a dynamic balance between active rust prevention and active chemical saving. The particle size of zinc carbonate particles is controlled within a limited range, which is beneficial for their uniform dispersion in the polyvinyl alcohol matrix and maintaining appropriate reactivity.

[0011] Preferably, the average pore size of the non-penetrating micropores in the directional hydrophobic breathing membrane layer is 0.1 to 0.5 μm; the core material of the organic phase change microcapsules in the phase change temperature regulating layer is paraffin wax, the wall material is melamine resin or urea-formaldehyde resin, and the phase change temperature is 35 to 45°C.

[0012] By adopting the above technical solution, the micropore size of the directional hydrophobic breathable membrane is within a range that allows vapor phase corrosion inhibitor molecules and water vapor molecules to pass freely, but prevents liquid water from penetrating by surface tension. This ensures that the vapor phase corrosion inhibitor always maintains a smooth diffusion channel inside the membrane, while condensation droplets are isolated on the outside of the breathable membrane and slide down the hydrophobic wall to the bottom of the packaging, without back-wetting or scouring the active layer. The paraffin core material in the phase change temperature regulating layer undergoes a solid-liquid phase change within the phase change temperature range, absorbing a large amount of latent heat, while the melamine resin or urea-formaldehyde resin wall material ensures the integrity and sealing of the microcapsules during processing and use. The selected phase change temperature range matches the temperature range at which the vapor phase corrosion inhibitor begins to volatilize violently. Through the thermal buffering effect, the peak temperature inside the membrane is controlled at a relatively gentle level, while providing a relatively stable temperature field for the sol-gel transformation of the inner ion-responsive self-locking interface layer, ensuring the orderly cycle of its current limiting and recovery process.

[0013] Secondly, this application provides a method for manufacturing a novel composite vapor phase rust inhibitor film, which adopts the following technical solution: A method for manufacturing a novel composite vapor phase rust inhibitor film includes the following steps: S1. Polypropylene is blended with β-crystal nucleating agent and extruded into sheets. The resulting sheets are stretched to obtain a directional hydrophobic breathable membrane base film with non-penetrating micropores. S2. An ion-responsive self-locking interface layer coating solution is coated on one surface of the directional hydrophobic breathing membrane base film, and dried to form an ion-responsive self-locking interface layer; the coating solution contains alginate derivatives, metal ion precipitation precursors and polyvinyl alcohol solution; S3. On the surface of the dried ion-responsive self-locking interface layer, a blend of intercalated modified layered double hydroxide and polyethylene is melted and formed into a film by extrusion casting to form a chloride ion triggered self-healing controlled release layer. S4. On the other surface of the directional hydrophobic breathing membrane base membrane, a phase change temperature regulating layer is formed by extrusion casting or coating of a blend material containing organic phase change microcapsules and polyolefins. S5. The novel composite vapor phase rust inhibitor film is obtained by winding.

[0014] By adopting the above technical solution, using a directional hydrophobic breathable membrane layer as the substrate, the remaining functional layers are sequentially constructed on both sides to achieve online continuous integral molding of each layer. First, a base membrane with non-penetrating micropores is obtained through a stretching pore-forming process. This base membrane has both skeletal support and gas-water separation functions. Then, an interface layer is coated and dried on one side of the base membrane to form an interface layer. A controlled-release layer is then extruded and cast on the interface layer to complete the construction of the inner protection sequence. A phase change temperature-regulating layer is formed on the other side of the base membrane to complete the construction of the outer thermal management layer. The entire manufacturing process does not require separate membrane fabrication followed by hot-pressing lamination, avoiding poor interlayer bonding and material waste caused by multiple offline lamination processes. The resulting membrane material has tight bonding between each layer and reliable functional connection.

[0015] Preferably, in step S1, the β-crystal nucleating agent is an aromatic amide or rare earth β-nucleating agent, and the amount added is 0.1% to 1% of the mass of polypropylene; the stretching temperature is 80 to 130°C, and the stretching ratio is 1.5 to 4 times.

[0016] By adopting the above technical solution, aromatic amide or rare earth β-nucleating agents induce polypropylene to form β-crystals during crystallization. During subsequent stretching, the β-crystals generate a uniformly distributed microporous structure through crystal transformation and lamellar separation, rather than through-holes. The stretching temperature is selected above the glass transition temperature of polypropylene and below its melting point, so that the sheet can obtain sufficient molecular chain mobility in a highly elastic state to form regular micropores. The stretching ratio is set to ensure that the generated micropore pore size is stable within the target range. The base film obtained by this process has both gas permeability and hydrophobic barrier properties against liquid water, providing a good foundation for the smoothness and bonding strength of subsequent interface layer coating and melt bonding.

[0017] Preferably, in step S2, the mass concentration of the polyvinyl alcohol solution is 5%–15%, the alginate derivative is sodium alginate or potassium alginate, the metal ion precipitation precursor is zinc carbonate microparticles; the drying temperature is 40–80°C, the drying time is 2–6 hours, and the dry thickness of the resulting ion-responsive self-locking interface layer is 5–20 μm.

[0018] By adopting the above technical solution, the concentration of polyvinyl alcohol solution is controlled within a moderate range, giving the coating liquid good leveling properties and forming a uniform wet film layer on the surface of the breathable membrane base. At the same time, excessive concentration is avoided, which would lead to excessive solution viscosity and be detrimental to thin-layer coating. Sodium alginate or potassium alginate is uniformly mixed with zinc carbonate particles in the polyvinyl alcohol solution, with the zinc carbonate particles stably suspended in the coating liquid in solid form. The drying temperature is selected above the evaporation temperature of water but far below the decomposition or denaturation temperature of each component, allowing water to gradually escape and form a polyvinyl alcohol microporous matrix, in which zinc carbonate particles and uniformly distributed alginate derivatives are embedded. The drying time is controlled to ensure that the residual moisture content is low enough, so that the interface layer maintains structural stability in the subsequent high-temperature melt casting step. When the resulting interface layer is in a dry microporous state, it allows gas phase corrosion inhibitor molecules to pass through, and local pore closure only occurs after being triggered by corrosion-inhibiting acid radicals.

[0019] Preferably, step S3 further includes a pretreatment for intercalation modification of the layered double hydroxide: dispersing the layered double hydroxide in a salt solution containing gaseous corrosion-inhibiting anions, reacting under stirring conditions, and then washing, drying, and grinding to obtain intercalated modified layered double hydroxide powder; in the blended material, the weight ratio of polyethylene to intercalated modified layered double hydroxide is 100:5 to 30; the extrusion casting temperature is 140 to 200°C.

[0020] By adopting the above technical solution, the intercalation modification pretreatment introduces organic carboxylate anions into the interlayer of layered double hydroxides through ion exchange, replacing the original inorganic interlayer anions. This allows the layered double hydroxides to retain their ability to capture chloride ions while becoming a solid carrier of corrosion-inhibiting anions. The washing step removes unexchanged residual salts, and the drying and grinding steps obtain powder with a particle size suitable for blending. The intercalated modified layered double hydroxides are then blended with polyethylene in a certain proportion and extruded and cast. The layered double hydroxide powder is fully coated and dispersed by the polyethylene melt, forming an inner film after cooling. The extrusion casting temperature is set within the processing window of polyethylene, ensuring good melt flowability while remaining below the interlayer structure destruction temperature of the intercalated modified layered double hydroxides, thus ensuring that the corrosion-inhibiting anions remain in the interlayer after processing. During the melt casting process, the polyethylene melt directly adheres to the surface of the dried and shaped ion-responsive self-locking interface layer, forming a tight interlayer bond.

[0021] Preferably, in step S4, the organic phase change microcapsules are prepared by in-situ polymerization or interfacial polymerization, with paraffin as the core material and melamine resin or urea-formaldehyde resin as the wall material, and the average particle size of the microcapsules is 1-20 μm; the processing temperature during extrusion casting or coating is controlled above the melting point of polyolefin and below the decomposition temperature of the microcapsule wall material.

[0022] By employing the above technical solutions, in-situ polymerization or interfacial polymerization forms a dense resin wall shell on the surface of paraffin droplets, giving the microcapsules a regular spherical morphology and uniform particle size distribution. The wall material maintains structural integrity during high-temperature processing, preventing core material leakage. Controlling the particle size within the specified range facilitates uniform dispersion of microcapsules in the polyolefin matrix and the continuity of subsequent film formation. The processing temperature is controlled above the temperature required for polyolefin melt processing to ensure melt flow and film uniformity, while not exceeding the thermal decomposition initiation temperature of the microcapsule wall material to avoid microcapsule rupture and failure. The microcapsules are uniformly embedded in the phase change temperature-regulating layer, and the film absorbs heat when the temperature rises to the paraffin melting range during use, playing a thermal buffering role.

[0023] Preferably, in step S5, after winding, the resulting film roll is left to stand for 12 to 72 hours in an environment with a temperature of 30 to 60°C and a relative humidity of 40% to 70%, so that the polyvinyl alcohol matrix in the ion-responsive self-locking interface layer can complete the moisture conditioning and stabilization.

[0024] By adopting the above technical solution, the wound film roll is in a state of incomplete equilibrium. During the film drying process, the polyvinyl alcohol matrix in the ion-responsive self-locking interface layer undergoes rapid dehydration, resulting in uneven local chain segment stacking and unstable micropore morphology. After being placed in a conditioned environment, the polyvinyl alcohol molecular chains absorb trace amounts of moisture and undergo conformational relaxation, making the micropore structure more uniform and improving the overall flexibility and dimensional stability of the film. The conditioned interface layer maintains its initial microporous state during storage and transportation. When a corrosion-inhibiting acid radical trigger signal occurs in the actual use environment, the cross-linking and pore-closing behavior of the alginate derivative and zinc ions occurs accurately as designed, thereby ensuring that the entire negative feedback regulation loop is reliably effective in practical applications.

[0025] In summary, this application has the following beneficial effects: 1. Because this application adopts a layered structure that combines a chloride ion-triggered self-healing controlled-release layer with an ion-responsive self-locking interface layer, it utilizes the selective capture of chloride ions by layered double hydroxides and the isocharge displacement release of corrosion-inhibiting anions. At the same time, by taking advantage of the behavior of alginate derivatives in the interface layer and dissolved metal ions, external chloride ion erosion is transformed into a trigger signal for the release of internal corrosion inhibitors and subsequent dosage limiting. This achieves integrated control of corrosion-responsive on-demand protection and automatic drug saving, and obtains the effect of autonomously adjusting the anti-rust supply and drug efficacy maintenance cycle in a dynamic corrosion environment.

[0026] 2. In this application, a directional hydrophobic breathing membrane layer is preferably used as the intermediate framework. By utilizing the differentiated permeability characteristics of gas molecules and liquid water through the non-penetrating microporous structure, the diffusion channels of the gas phase corrosion inhibitor are separated from the condensate water phase, avoiding the erosion and loss of active components in the membrane by condensate water. At the same time, it provides a stable physical boundary for the chemical response of the inner interface layer that is not disturbed by liquid water, thus achieving the effect of no loss of rust-preventing components and no failure of response function under repeated condensation conditions.

[0027] 3. The method of this application uses a directional hydrophobic breathable membrane layer as a substrate and sequentially constructs an interface layer, a controlled release layer and a temperature-regulating layer online, so that each functional layer is bonded together layer by layer during the continuous molding process, eliminating the need for hot-pressing lamination after separate film preparation, avoiding interlayer bonding defects caused by offline lamination, and achieving the effect of tight connection between layers and smooth functional transfer.

[0028] 4. This application adopts a four-layer synergistic design consisting of a chloride ion-triggered self-healing controlled-release layer, an ion-responsive self-locking interface layer, a directional hydrophobic breathing membrane layer, and a phase change temperature-regulating layer. This design enables chemical self-regulation, gas-liquid physical separation, and thermal buffering functions to rely on each other. The breathing membrane layer ensures the responsive environment of the interface layer, while the temperature-regulating layer smooths temperature fluctuations, allowing the sol-gel transformation of the interface layer to proceed in an orderly manner. This establishes a coherent protection chain from corrosion detection to agent regulation and environmental stability, achieving continuous and effective rust prevention for metal parts under marine transportation and humid, hot, and salt spray conditions. Attached Figure Description

[0029] Figure 1 This is a flowchart illustrating a method for manufacturing a novel composite vapor phase rust inhibitor film as proposed in this application. Figure 2 This is a schematic diagram showing the test results of chloride ion-triggered corrosion inhibition response and self-regulation performance in the embodiments and comparative examples of this application; Figure 3 This is a schematic diagram showing the test results of condensation flushing retention performance of the embodiments and comparative examples in this application; Figure 4 This is a schematic diagram showing the long-term rust prevention performance test results under combined working conditions of the embodiments and comparative examples in this application. Detailed Implementation

[0030] The present application will be further described in detail below with reference to the accompanying drawings and embodiments.

[0031] Technical concept: This application discloses a novel composite vapor phase rust inhibitor film and its manufacturing method. It comprises a chloride ion-triggered self-healing controlled-release layer, an ion-responsive self-locking interface layer, a directional hydrophobic breathable membrane layer, and a phase change temperature-regulating layer, stacked sequentially. The preparation method is as follows: S1, polypropylene is blended with a β-crystal nucleating agent, extruded and cast into a sheet, and stretched to obtain a base film; S2, an ion-responsive self-locking interface layer coating liquid is applied to the surface of the base film and dried to form an interface layer; S3, on the surface of the dried interface layer, the blended material is melted and cast by extrusion to form a self-healing controlled-release layer; S4, on the other surface of the base film, the blended material is cast by extrusion or coating to form a phase change temperature-regulating layer; S5, the novel composite vapor phase rust inhibitor film is obtained by winding.

[0032] This application employs a layered structure combining a chloride ion-triggered self-healing controlled-release layer and an ion-responsive self-locking interface layer. It utilizes the selective capture of chloride ions by layered double hydroxides and the isocharge displacement release of corrosion-inhibiting anions. Simultaneously, by leveraging the behavior of alginate derivatives in the interface layer and dissolved metal ions, external chloride ion erosion is transformed into a trigger signal for the release of internal corrosion inhibitors and subsequent dosage limiting. This achieves integrated control of corrosion-responsive on-demand protection and automatic chemical saving, resulting in the effect of autonomously adjusting the rust prevention supply and the duration of efficacy maintenance in dynamic corrosion environments.

[0033] Example 1: This example provides a novel composite vapor phase rust inhibitor film, comprising a chloride ion-triggered self-healing controlled-release layer, an ion-responsive self-locking interface layer, a directional hydrophobic breathable membrane layer, and a phase change temperature-regulating layer stacked sequentially; wherein, the chloride ion-triggered self-healing controlled-release layer comprises the following raw materials in parts by weight: 80 parts polyethylene, 5 parts intercalated modified layered double hydroxide; vapor phase corrosion-inhibiting anions are inserted between the intercalated modified layered double hydroxide layers; the ion-responsive self-locking interface layer comprises the following raw materials in parts by weight: 80 parts polyvinyl alcohol, 10 parts alginate derivative, 5 parts metal ion precipitation precursor; the directional hydrophobic breathable membrane layer comprises the following raw materials in parts by weight: 80 parts polypropylene, 0.1 parts β crystal nucleating agent, and the directional hydrophobic breathable membrane layer is a porous membrane with non-penetrating micropores; the phase change temperature-regulating layer comprises the following raw materials in parts by weight: 80 parts polyolefin, 10 parts organic phase change microcapsules.

[0034] Among them, the gas-phase corrosion-inhibiting anion is selected from benzoate; the layered double hydroxide is magnesium aluminum layered double hydroxide.

[0035] In the ion-responsive self-locking interface layer, the alginate derivative is sodium alginate, and the metal ion precipitation precursor is zinc carbonate microparticles; the average particle size of the zinc carbonate microparticles is 0.5 μm; and the degree of alcoholysis of polyvinyl alcohol is 86%.

[0036] The average pore size of the non-penetrating micropores in the directional hydrophobic breathing membrane layer is 0.1 μm; the core material of the organic phase change microcapsules in the phase change temperature regulating layer is paraffin wax, the wall material is melamine resin, and the phase change temperature is 35℃.

[0037] The above-mentioned method for manufacturing a novel composite vapor phase rust inhibitor film includes the following steps: S1. Polypropylene is blended with a β-crystal nucleating agent, extruded and cast into sheets, and the resulting sheets are stretched to obtain a directional hydrophobic breathable membrane base film with non-penetrating micropores.

[0038] The β-crystal nucleating agent is an aromatic amide β-nucleating agent, and the amount added is 0.1% of the mass of polypropylene; the stretching temperature is 80℃, and the stretching ratio is 1.5 times.

[0039] S2. An ion-responsive self-locking interface layer coating solution is coated on one surface of the directional hydrophobic breathing membrane base membrane, and then dried to form an ion-responsive self-locking interface layer; the coating solution contains alginate derivatives, metal ion precipitation precursors and polyvinyl alcohol solution.

[0040] The polyvinyl alcohol solution had a mass concentration of 5%, the alginate derivative was sodium alginate, and the metal ion precipitation precursor was zinc carbonate microparticles; the drying temperature was 40℃, and the drying time was 2 hours; the dry thickness of the resulting ion-responsive self-locking interface layer was 5 μm.

[0041] S3. On the surface of the dried ion-responsive self-locking interface layer, a blend of intercalated modified layered double hydroxide and polyethylene is melted and cast by extrusion to form a chloride ion-triggered self-healing controlled-release layer.

[0042] The pretreatment for intercalation modification of layered double hydroxides involves dispersing the layered double hydroxides in a salt solution containing gaseous corrosion-inhibiting anions and reacting them under stirring conditions. After the reaction, the mixture is washed, dried, and ground to obtain intercalated modified layered double hydroxide powder. In the blended material, the weight ratio of polyethylene to intercalated modified layered double hydroxides is 100:5. The extrusion casting temperature is 140℃.

[0043] S4. On the other surface of the directional hydrophobic breathing membrane base membrane, a blend of organic phase change microcapsules and polyolefins is formed by extrusion casting or coating to form a phase change temperature regulating layer.

[0044] The organic phase change microcapsules were prepared by in-situ polymerization. The core material was paraffin wax and the wall material was melamine resin. The average particle size of the microcapsules was 1 μm. The extrusion casting process temperature was controlled above the melting point of polyolefin and below the decomposition temperature of the microcapsule wall material.

[0045] S5. The new composite vapor phase rust-preventive film is obtained by rewinding.

[0046] After winding, the resulting film roll is left to stand for 12 hours in an environment with a temperature of 30°C and a relative humidity of 40% to allow the polyvinyl alcohol matrix in the ion-responsive self-locking interface layer to complete the moisture conditioning and stabilization.

[0047] Example 2: This example provides a novel composite vapor phase rust inhibitor film, comprising a chloride ion-triggered self-healing controlled-release layer, an ion-responsive self-locking interface layer, a directional hydrophobic breathable membrane layer, and a phase change temperature-regulating layer stacked sequentially; wherein, the chloride ion-triggered self-healing controlled-release layer comprises the following raw materials in parts by weight: 100 parts polyethylene, 17.5 parts intercalated modified layered double hydroxide; vapor phase corrosion-inhibiting anions are intercalated between the intercalated modified layered double hydroxide layers; the ion-responsive self-locking interface layer comprises the following raw materials in parts by weight: 100 parts polyvinyl alcohol, 25 parts alginate derivative, 12.5 parts metal ion precipitation precursor; the directional hydrophobic breathable membrane layer comprises the following raw materials in parts by weight: 100 parts polypropylene, 1.05 parts β crystal nucleating agent, and the directional hydrophobic breathable membrane layer is a porous membrane with non-penetrating micropores; the phase change temperature-regulating layer comprises the following raw materials in parts by weight: 100 parts polyolefin, 30 parts organic phase change microcapsules.

[0048] Among them, the gas-phase corrosion-inhibiting anion is selected from a mixture of caprylate and laurate; the layered double hydroxide is zinc-aluminum layered double hydroxide.

[0049] In the ion-responsive self-locking interface layer, the alginate derivative is potassium alginate, and the metal ion precipitation precursor is zinc carbonate microparticles; the average particle size of the zinc carbonate microparticles is 2.75 μm; and the degree of alcoholysis of polyvinyl alcohol is 90%.

[0050] The average pore size of the non-penetrating micropores in the directional hydrophobic breathing membrane is 0.3 μm; the core material of the organic phase change microcapsules in the phase change temperature regulating layer is paraffin wax, the wall material is urea-formaldehyde resin, and the phase change temperature is 40℃.

[0051] The above-mentioned method for manufacturing a novel composite vapor phase rust inhibitor film includes the following steps: S1. Polypropylene is blended with a β-crystal nucleating agent, extruded and cast into sheets, and the resulting sheets are stretched to obtain a directional hydrophobic breathable membrane base film with non-penetrating micropores.

[0052] The β-crystal nucleating agent is a rare earth β-nucleating agent, and its addition amount is 0.55% of the mass of polypropylene; the stretching temperature is 105℃, and the stretching ratio is 2.75 times.

[0053] S2. An ion-responsive self-locking interface layer coating solution is coated on one surface of the directional hydrophobic breathing membrane base membrane, and then dried to form an ion-responsive self-locking interface layer; the coating solution contains alginate derivatives, metal ion precipitation precursors and polyvinyl alcohol solution.

[0054] The polyvinyl alcohol solution had a mass concentration of 10%, the alginate derivative was potassium alginate, and the metal ion precipitation precursor was zinc carbonate microparticles; the drying temperature was 60℃, and the drying time was 4 hours; the dry thickness of the resulting ion-responsive self-locking interface layer was 12.5 μm.

[0055] S3. On the surface of the dried ion-responsive self-locking interface layer, a blend of intercalated modified layered double hydroxide and polyethylene is melted and cast by extrusion to form a chloride ion-triggered self-healing controlled-release layer.

[0056] The pretreatment for intercalation modification of layered double hydroxides involves dispersing the layered double hydroxides in a salt solution containing gaseous corrosion-inhibiting anions and reacting them under stirring conditions. After the reaction, the mixture is washed, dried, and ground to obtain intercalated modified layered double hydroxide powder. In the blended material, the weight ratio of polyethylene to intercalated modified layered double hydroxides is 100:17.5. The extrusion casting temperature is 170℃.

[0057] S4. On the other surface of the directional hydrophobic breathing membrane base membrane, a blend of organic phase change microcapsules and polyolefins is formed by extrusion casting or coating to form a phase change temperature regulating layer.

[0058] The organic phase change microcapsules were prepared by interfacial polymerization. The core material was paraffin wax and the wall material was urea-formaldehyde resin. The average particle size of the microcapsules was 10.5 μm. The coating process temperature was controlled above the melting point of polyolefin and below the decomposition temperature of the microcapsule wall material.

[0059] S5. The new composite vapor phase rust-preventive film is obtained by rewinding.

[0060] The process involves placing the resulting film roll at 45°C and 55% relative humidity for 42 hours after winding to allow the polyvinyl alcohol matrix in the ion-responsive self-locking interface layer to complete the humidity conditioning and stabilization.

[0061] Example 3: This example provides a novel composite vapor phase rust inhibitor film, comprising a chloride ion-triggered self-healing controlled-release layer, an ion-responsive self-locking interface layer, a directional hydrophobic breathable membrane layer, and a phase change temperature-regulating layer stacked sequentially; wherein, the chloride ion-triggered self-healing controlled-release layer comprises the following raw materials in parts by weight: 120 parts of polyethylene, 30 parts of intercalated modified layered double hydroxide; vapor phase corrosion-inhibiting anions are intercalated between the intercalated modified layered double hydroxide layers; the ion-responsive self-locking interface layer comprises the following raw materials in parts by weight: 120 parts of polyvinyl alcohol, 40 parts of alginate derivative, and 20 parts of metal ion precipitation precursor; the directional hydrophobic breathable membrane layer comprises the following raw materials in parts by weight: 120 parts of polypropylene, 2 parts of β-crystal nucleating agent, and the directional hydrophobic breathable membrane layer is a porous membrane with non-penetrating micropores; the phase change temperature-regulating layer comprises the following raw materials in parts by weight: 120 parts of polyolefin, and 50 parts of organic phase change microcapsules.

[0062] Among them, the gas-phase corrosion-inhibiting anion is selected from cinnamate; the layered double hydroxide is magnesium aluminum layered double hydroxide.

[0063] In the ion-responsive self-locking interface layer, the alginate derivative is sodium alginate, and the metal ion precipitation precursor is zinc carbonate microparticles; the average particle size of the zinc carbonate microparticles is 5 μm; and the degree of alcoholysis of polyvinyl alcohol is 99%.

[0064] The average pore size of the non-penetrating micropores in the directional hydrophobic breathing membrane layer is 0.5 μm; the core material of the organic phase change microcapsules in the phase change temperature regulating layer is paraffin wax, the wall material is melamine resin, and the phase change temperature is 45℃.

[0065] The above-mentioned method for manufacturing a novel composite vapor phase rust inhibitor film includes the following steps: S1. Polypropylene is blended with a β-crystal nucleating agent, extruded and cast into sheets, and the resulting sheets are stretched to obtain a directional hydrophobic breathable membrane base film with non-penetrating micropores.

[0066] The β-crystal nucleating agent is an aromatic amide β-nucleating agent, and the amount added is 1% of the mass of polypropylene; the stretching temperature is 130℃, and the stretching ratio is 4 times.

[0067] S2. An ion-responsive self-locking interface layer coating solution is coated on one surface of the directional hydrophobic breathing membrane base membrane, and then dried to form an ion-responsive self-locking interface layer; the coating solution contains alginate derivatives, metal ion precipitation precursors and polyvinyl alcohol solution.

[0068] The polyvinyl alcohol solution had a mass concentration of 15%, the alginate derivative was sodium alginate, and the metal ion precipitation precursor was zinc carbonate microparticles; the drying temperature was 80℃, and the drying time was 6 hours; the dry thickness of the resulting ion-responsive self-locking interface layer was 20 μm.

[0069] S3. On the surface of the dried ion-responsive self-locking interface layer, a blend of intercalated modified layered double hydroxide and polyethylene is melted and cast by extrusion to form a chloride ion-triggered self-healing controlled-release layer.

[0070] The pretreatment for intercalation modification of layered double hydroxides involves dispersing the layered double hydroxides in a salt solution containing gaseous corrosion-inhibiting anions and reacting them under stirring conditions. After the reaction, the mixture is washed, dried, and ground to obtain intercalated modified layered double hydroxide powder. In the blended material, the weight ratio of polyethylene to intercalated modified layered double hydroxides is 100:30. The extrusion casting temperature is 200℃.

[0071] S4. On the other surface of the directional hydrophobic breathing membrane base membrane, a blend of organic phase change microcapsules and polyolefins is formed by extrusion casting or coating to form a phase change temperature regulating layer.

[0072] Among them, the organic phase change microcapsules are prepared by in-situ polymerization, with paraffin as the core material and melamine resin as the wall material. The average particle size of the microcapsules is 20μm. The extrusion casting process temperature is controlled above the melting point of polyolefin and below the decomposition temperature of the microcapsule wall material.

[0073] S5. The new composite vapor phase rust-preventive film is obtained by rewinding.

[0074] After winding, the resulting film roll is left to stand for 72 hours in an environment with a temperature of 60°C and a relative humidity of 70% to allow the polyvinyl alcohol matrix in the ion-responsive self-locking interface layer to complete the humidity conditioning and stabilization.

[0075] Comparative Example 1: This comparative example refers to the content of Example 1, except that an equal amount of unintercalated layered double hydroxide is used to replace the intercalated modified layered double hydroxide in the chloride ion triggered self-healing controlled release layer, that is, no gas-phase corrosion-inhibiting anions are inserted between the layers of the layered double hydroxide. The rest is the same as Example 1.

[0076] Comparative Example 2: This comparative example refers to the content of Example 1, except that an equal amount of calcium carbonate microparticles are used to replace the zinc carbonate microparticles, the precursor of metal ion precipitation, in the ion-responsive self-locking interface layer. The rest of the content is the same as that of Example 1.

[0077] Comparative Example 3: This comparative example refers to the content of Example 1, except that an equal amount of polyvinylpyrrolidone is used to replace the alginate derivative in the ion-responsive self-locking interface layer, and the rest is the same as Example 1.

[0078] Comparative Example 4: This comparative example refers to the content of Example 1, except that the directional hydrophobic breathable membrane layer is replaced with an equal amount of ordinary polypropylene cast film instead of polypropylene stretched film with non-penetrating micropores. That is, the directional hydrophobic breathable membrane layer is a solid membrane layer without pores. The rest of the content is the same as that of Example 1.

[0079] Comparative Example 5: This comparative example refers to the content of Example 1, except that an equal amount of unencapsulated paraffin powder is used to replace the organic phase change microcapsules in the phase change temperature regulating layer, that is, the paraffin is dispersed in the polyolefin matrix in an exposed form. The rest is the same as Example 1.

[0080] Comparative Example 6: This comparative example refers to the content of Example 1, except that each membrane layer is fabricated separately and then hot-pressed to replace the manufacturing method of sequentially constructing each layer online with the directional hydrophobic breathable membrane layer as the substrate. That is, four thin films, namely, chloride ion triggered self-healing controlled release layer, ion-responsive self-locking interface layer, directional hydrophobic breathable membrane layer and phase change temperature regulation layer, are first fabricated separately, and then the four thin films are sequentially bonded together by hot-pressing. The rest of the content is the same as in Example 1.

[0081] Performance testing Sample preparation: Novel composite vapor phase rust inhibitor samples were prepared according to the formulations and manufacturing methods described in each embodiment and comparative example. Several pieces of each sample were taken and cut into specimens with a length of 200 mm and a width of 150 mm. The specimens were placed in an environment with a temperature of 23°C and a relative humidity of 50% for 24 hours for later use. At the same time, several pieces of No. 45 steel with a length of 100 mm, a width of 50 mm and a thickness of 2 mm were prepared and treated with grinding to remove rust and acetone degreasing, as the metal substrate to be protected.

[0082] Chloride ion-triggered corrosion inhibition response and self-regulating performance testing: Vapor phase corrosion inhibitor film samples from each embodiment and comparative example were prepared into sealed test bags. 45# steel test pieces were suspended inside the bags. A mist containing trace amounts of chloride ions was pre-injected into the bags and evenly distributed. The entire test bag was placed in a constant temperature chamber at 50°C for 72 hours. After the test, the test pieces were removed, and the surface corrosion was visually observed and recorded. Simultaneously, the remaining vapor phase corrosion inhibitor within the film was extracted and its retention rate was measured to evaluate the corrosion inhibition response efficiency and self-regulating flow-limiting effect under chloride ion-triggered conditions. This test was conducted in accordance with the relevant provisions of GB / T19532 "Vapor Phase Corrosion Inhibiting Packaging Materials" and SH / T0533 "Vapor Phase Corrosion Inhibitors".

[0083] Performance testing of rust inhibitor retention under condensation and erosion conditions: Vapor phase corrosion inhibitor film samples from each embodiment and comparative example were prepared into sealed test bags. A 45# steel test piece was suspended inside the bag. The test bags were placed in a hot-cold alternating test chamber, cycling between 25°C and 65°C for 6 hours per cycle, for a total of 10 cycles. This allowed repeated condensation to form on the inner wall of the bag, which then slid down and collected along the film surface. After the test, the accumulated liquid at the bottom of the bag was collected, and the content of the vapor phase corrosion inhibitor component was tested. Simultaneously, the test piece was removed to observe whether there were any localized rust spots on the surface caused by erosion. This test was conducted in accordance with the relevant provisions of GB / T2423.34 "Environmental Testing for Electrical and Electronic Products - Part 2: Test Methods - Test Z / AD: Temperature / Humidity Combined Cyclic Test" and GB / T19532 "Vapor Phase Corrosion Inhibiting Packaging Materials".

[0084] Test on the heat-induced loss inhibition performance of corrosion inhibitors under high temperature conditions: The vapor phase corrosion inhibitor film samples of each embodiment and comparative example were placed in sealed containers without metal test pieces. The sealed containers were placed in a constant temperature oven at 65°C for 14 days. After the test, the film samples were taken out, the residual vapor phase corrosion inhibitor in the film was extracted and its loss rate was measured. This test was carried out in accordance with the relevant provisions of GB / T19532 "Vapor Phase Corrosion Inhibiting Packaging Materials".

[0085] Interlayer bonding strength and functional transfer performance testing: Vapor phase corrosion inhibitor film samples from each embodiment and comparative example were cut into strips 100 mm in length and 25 mm in width. Interlayer peel strength was tested on a material testing machine at a peeling speed of 100 mm / min. The peel force values ​​at the separation of each layer were recorded, and the failure morphology of the separation interface was observed to evaluate the degree of interlayer bonding strength. Simultaneously, samples of each peeled film layer were taken to test the residual vapor phase corrosion inhibitor content and the retention of functional component activity. This test was conducted in accordance with the relevant provisions of GB / T8808 "Peel Test Method for Flexible Composite Plastic Materials".

[0086] Long-term rust prevention performance testing under combined working conditions: Vapor phase rust inhibitor samples from each embodiment and comparative example were prepared into sealed test bags. A 45# steel test piece was suspended inside each bag. The test bags were placed in an alternating damp heat salt spray test chamber. A test procedure of 30 cycles was performed, maintaining the temperature at 40°C and relative humidity for 8 hours, followed by maintaining it at 25°C and relative humidity for 16 hours. During the test, the time of rust appearance and the extent of rust expansion were observed and recorded periodically. This test was conducted in accordance with the relevant provisions of GB / T10125 "Artificial Atmosphere Corrosion Test - Salt Spray Test" and GB / T2423.3 "Environmental Testing - Part 2: Test Methods - Cab: Constant Damp Heat Test".

[0087] Table 1: Chloride ion-triggered corrosion inhibition response, self-regulating performance, and condensation scouring retention performance Table 2: Corrosion Inhibitor Loss Suppression Performance and Interlayer Bonding Strength under High Temperature Conditions Table 3: Long-term rust prevention performance under combined working conditions Example Conclusion: See appendix Figure 1 ~Attached Figure 4 Based on the technical solutions of the embodiments and comparative examples, the following conclusions are drawn: Based on Examples 1 to 3 and Comparative Example 1, and in conjunction with Tables 1 and 3, it can be seen that when the chloride ion-triggered self-healing controlled-release layer uses unmodified layered double hydroxides, there are no exchangeable gaseous corrosion-inhibiting anions between the layers. After chloride ions invade, they are only captured and cannot trigger the displacement release of the corrosion inhibitor, resulting in no effective corrosion-inhibiting components volatilizing to the metal surface, and the rust prevention function is completely lost. At the same time, since the inner layer does not release corrosion-inhibiting acid radicals, the ion-responsive self-locking interface layer is always in the initial microporous state, and the entire negative feedback regulation loop cannot be activated. The rust prevention performance of the film under chloride ion environment and combined working conditions is significantly deteriorated. Therefore, the intercalation modification of layered double hydroxides endows the film with corrosion-triggered release function, which is the basis for the chloride ion-triggered self-healing controlled-release layer to play its on-demand protection role, and forms a cascade response with the interface layer.

[0088] Based on Examples 1 to 3 and Comparative Example 2, and in conjunction with Tables 1 and 2, it can be seen that when calcium carbonate microparticles replace zinc carbonate microparticles as the metal ion precipitation precursor in the ion-responsive self-locking interface layer, calcium carbonate is difficult to dissolve cross-linking active metal ions in the weakly acidic microenvironment formed by the corrosion-inhibiting acid anions. Alginic acid derivatives cannot undergo ion cross-linking to form a gel network. The interface layer retains its original porous state after the corrosion inhibitor is released, failing to restrict gas flow through the channels, leading to continuous leakage of the corrosion inhibitor and increased loss under high-temperature conditions. Therefore, the dissolution of zinc ions by zinc carbonate microparticles triggered by the corrosion-inhibiting acid anions and their cross-linking with the alginate derivatives to close the pores is the core element for achieving the self-locking flow-limiting function of the interface layer, directly impacting drug efficacy maintenance and drug-saving regulation.

[0089] Based on Examples 1 to 3 and Comparative Example 3, and in conjunction with Tables 1 and 2, it can be seen that when polyvinylpyrrolidone replaces the alginate derivative in the ion-responsive self-locking interface layer, the polyvinylpyrrolidone molecular chain lacks carboxyl groups that participate in ion crosslinking. Even if zinc carbonate dissolves zinc ions under the action of corrosion-inhibiting acid radicals, a three-dimensional gel network cannot be formed. The interface layer loses its ability to regulate pores under triggering conditions, and the failure of flow restriction causes excessive leakage of the corrosion inhibitor at high temperatures and during long-term use, reducing the utilization rate of the rust-preventing component. Therefore, the alginate derivative, through the crosslinking reaction between its carboxyl groups and zinc ions, endows the interface layer with reversible pore regulation capabilities, which is the structural basis for achieving release-induced flow restriction after corrosion-triggered release.

[0090] Based on Examples 1 to 3 and Comparative Example 4, and in conjunction with Tables 1 and 3, it can be seen that when the directional hydrophobic breathable membrane layer uses a non-porous solid polypropylene cast film to replace the stretched film with non-penetrating micropores, the diffusion channels of the vapor phase corrosion inhibitor molecules are blocked, making it difficult for the corrosion inhibitor to effectively migrate from the inner layer to the metal surface, thus inhibiting the rust prevention effect in the early stages. At the same time, the solid film layer does not have gas-liquid separation function, and the water film formed by condensation on the inner surface of the membrane cannot be channeled away, washing away the active components in the inner layer and interfering with the chemical response environment of the interface layer. Under alternating condensation conditions, the rust prevention ability is significantly reduced. Therefore, the non-penetrating microporous structure of the directional hydrophobic breathable membrane layer not only ensures the smooth diffusion channels of the vapor phase corrosion inhibitor but also isolates the liquid condensation from the active layer, providing a stable boundary for the inner chemical response that is not disturbed by liquid water.

[0091] Based on Examples 1 to 3 and Comparative Example 5, and in conjunction with Tables 2 and 3, it can be seen that when unencapsulated paraffin powder replaces the organic phase change microcapsules in the phase change temperature regulation layer, the paraffin melts and seeps out during high-temperature processing, leading to film adhesion and loss of the microcapsule structure. The phase change temperature regulation function is significantly lost after processing. In high-temperature storage and transportation environments, the internal temperature of the film rises rapidly with the external environment, making it difficult to suppress the evaporation rate of the corrosion inhibitor, resulting in a sharp increase in heat-induced loss. Simultaneously, exposed paraffin migrates and diffuses within the polyolefin matrix, affecting the interlayer bonding stability between the interface layer and the temperature regulation layer. Therefore, the wall encapsulation of the organic phase change microcapsules ensures the integrity and reversible phase change capability of the phase change material during processing and use, which is a structural prerequisite for suppressing heat-induced loss of the corrosion inhibitor under high-temperature conditions.

[0092] As can be seen from Examples 1 to 3 and Comparative Example 6, and Tables 2 and 3, when each film layer is manufactured by separate film preparation followed by hot-pressing, each layer is already shaped before hot pressing. At the composite interface, local unbonded or weakly bonded areas are easily generated due to surface roughness, residual stress, or deviations in hot-pressing parameters. The interlayer peel strength is significantly lower than that of the online layer-by-layer bonding method. Repeated heating and pressurization during offline bonding can also lead to the attenuation of the activity of functional components in the formed film layer. After peeling, the residual corrosion inhibitor content and functional activity of each layer are lost. Therefore, the manufacturing method of constructing each functional layer online in sequence with a directional hydrophobic breathable film layer as the substrate forms a tight interlayer bond through direct bonding during melt flow delay, reducing the damage to functional components caused by repeated thermal processes and ensuring the effective transfer and connection of functions of each layer.

[0093] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A novel composite vapor phase rust inhibitor film, characterized in that, The material comprises, in sequence, a chloride ion-triggered self-healing controlled-release layer, an ion-responsive self-locking interface layer, a directional hydrophobic breathing membrane layer, and a phase change temperature-regulating layer. The chloride ion-triggered self-healing controlled-release layer contains the following raw materials in parts by weight: 80-120 parts polyethylene and 5-30 parts intercalated modified layered double hydroxides; the intercalated modified layered double hydroxides contain intercalated gas-phase corrosion-inhibiting anions. The ion-responsive self-locking interface layer contains the following raw materials in parts by weight: 80-120 parts polyvinyl alcohol, 10-40 parts alginate derivative, and 5-20 parts a metal ion precipitation precursor. The directional hydrophobic breathing membrane layer contains the following raw materials in parts by weight: 80-120 parts polypropylene and 0.1-2 parts β-crystal nucleating agent, and the directional hydrophobic breathing membrane layer is a porous membrane with non-penetrating micropores. The phase change temperature-regulating layer contains the following raw materials in parts by weight: 80-120 parts polyolefin and 10-50 parts organic phase change microcapsules.

2. The novel composite vapor phase rust inhibitor film according to claim 1, characterized in that, The gas-phase corrosion-inhibiting anion is selected from one or more of benzoate, caprylate, laurate, or cinnamate; the layered double hydroxide is a magnesium-aluminum layered double hydroxide or a zinc-aluminum layered double hydroxide.

3. The novel composite vapor phase rust inhibitor film according to claim 1, characterized in that, In the ion-responsive self-locking interface layer, the alginate derivative is sodium alginate or potassium alginate, and the metal ion precipitation precursor is zinc carbonate microparticles; the average particle size of the zinc carbonate microparticles is 0.5-5 μm; and the degree of alcoholysis of the polyvinyl alcohol is greater than 85%.

4. The novel composite vapor phase rust inhibitor film according to claim 1, characterized in that, The average pore size of the non-penetrating micropores in the directional hydrophobic breathing membrane is 0.1–0.5 μm; the core material of the organic phase change microcapsules in the phase change temperature regulating layer is paraffin wax, the wall material is melamine resin or urea-formaldehyde resin, and the phase change temperature is 35–45 °C.

5. A method for manufacturing a novel composite vapor phase rust inhibitor film, characterized in that, A novel composite vapor phase rust inhibitor film according to any one of claims 1-4 comprises the following steps: S1. Polypropylene is blended with β-crystal nucleating agent and extruded into sheets. The resulting sheets are stretched to obtain a directional hydrophobic breathable membrane base film with non-penetrating micropores. S2. An ion-responsive self-locking interface layer coating solution is applied to one surface of the directional hydrophobic breathing membrane base film, and then dried to form an ion-responsive self-locking interface layer; the coating solution contains alginate derivatives, metal ion precipitation precursors and polyvinyl alcohol solution; S3. On the surface of the dried ion-responsive self-locking interface layer, a blend of intercalated modified layered double hydroxide and polyethylene is melted and formed into a film by extrusion casting to form a chloride ion triggered self-healing controlled release layer. S4. On the other surface of the directional hydrophobic breathing membrane base membrane, a phase change temperature regulating layer is formed by extrusion casting or coating of a blend material containing organic phase change microcapsules and polyolefins. S5. The novel composite vapor phase rust inhibitor film is obtained by winding.

6. The method for manufacturing a novel composite vapor phase rust inhibitor film according to claim 5, characterized in that, In step S1, the β-crystal nucleating agent is an aromatic amide or rare earth β-nucleating agent, and the amount added is 0.1% to 1% of the mass of polypropylene; the stretching temperature is 80 to 130°C, and the stretching ratio is 1.5 to 4 times.

7. The method for manufacturing a novel composite vapor phase rust inhibitor film according to claim 5, characterized in that, In step S2, the mass concentration of the polyvinyl alcohol solution is 5%–15%, the alginate derivative is sodium alginate or potassium alginate, and the metal ion precipitation precursor is zinc carbonate microparticles; the drying temperature is 40–80°C, and the drying time is 2–6 hours; the dry thickness of the resulting ion-responsive self-locking interface layer is 5–20 μm.

8. The method for manufacturing a novel composite vapor phase rust inhibitor film according to claim 5, characterized in that, Step S3 also includes a pretreatment for intercalation modification of the layered double hydroxide: the layered double hydroxide is dispersed in a salt solution containing gaseous corrosion-inhibiting anions, and reacted under stirring conditions. After the reaction, it is washed, dried, and ground to obtain intercalated modified layered double hydroxide powder. In the blended material, the weight ratio of polyethylene to intercalated modified layered double hydroxide is 100:5 to 30. The extrusion casting temperature is 140 to 200°C.

9. The method for manufacturing a novel composite vapor phase rust inhibitor film according to claim 5, characterized in that, In step S4, the organic phase change microcapsules are prepared by in-situ polymerization or interfacial polymerization. The core material is paraffin wax, and the wall material is melamine resin or urea-formaldehyde resin. The average particle size of the microcapsules is 1-20 μm. When extruding, casting, or coating, the processing temperature is controlled above the melting point of polyolefin and below the decomposition temperature of the microcapsule wall material.

10. The method for manufacturing a novel composite vapor phase rust inhibitor film according to claim 5, characterized in that, In step S5, after winding, the resulting film roll is left to stand for 12 to 72 hours in an environment with a temperature of 30 to 60°C and a relative humidity of 40% to 70%, so that the polyvinyl alcohol matrix in the ion-responsive self-locking interface layer can complete the moisture conditioning and stabilization.